Partisipasi Anggaran dan Implementasi Sistem Informasi Akuntansi Terhadap Kinerja Manajerial - Yudista, Ofan Maulana; SE, Amilin; SE, Surtikanti (Jurnal Manajemen, 2016)
This research analyzes some factors that influence managerial performance. This research focus on participation of estimates on their had and implementation of accounting information system. Sample in this research using purpostive sampling that appropriate with the criteria till using the sample as many as 86 samples. The result of the research shows that budget participation has a significance possitive effect (direct) to magerial performance directly. Accounting Information System has a significance possitive effect to managerial performance directly. Budget participation has a significance possitive effect to managerial performance trough accounting information system indirectly. Accounting information system has a significance possitive effect to managerial performance trough budget participation as an intervening variable indirectly